Preparation method of high-density super-high-thermal-conductivity aluminum nitride ceramic substrate

CN122916686APending Publication Date: 2026-10-16YANGZHOU XIAOTIAN PHOTOSKOT TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611287585.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-24
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0004]针对现有技术的不足,本发明提供了一种高致密度超高导热氮化铝陶瓷基板的制备方法,该发明要解决的技术问题是:通过优化粉体表面改性、复合烧结助剂的添加以及烧结与成型工艺,解决常压烧结难以兼顾导热与致密度、热压烧结设备成本高、传统粉体预处理工艺去除杂质不充分的问题

Benefits of technology

该高致密度超高导热氮化铝陶瓷基板的制备方法,通过精细的表面改性、复合烧结助剂的添加和严格控制烧结过程,提高了氮化铝陶瓷基板的致密度和导热性能,向氮化铝粉体加入表面改性剂和复合烧结助剂,减少了孔隙率,并通过低温致密化烧结优化了晶粒结构,避免了导热性差的玻璃相包裹晶粒,提升了基板的导热率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916686A_ABST
    Figure CN122916686A_ABST
Patent Text Reader

Abstract

The application provides a preparation method of high-density super-high-thermal-conductivity aluminum nitride ceramic substrate and relates to the technical field of ceramic substrate preparation. The preparation method of the high-density super-high-thermal-conductivity aluminum nitride ceramic substrate comprises the following steps: selecting aluminum nitride powder, adding a surface modifier to the aluminum nitride powder and ball milling in an anhydrous ethanol medium to obtain slurry, performing solid-liquid separation and drying treatment on the slurry and sieving to obtain modified aluminum nitride powder. The preparation method of the high-density super-high-thermal-conductivity aluminum nitride ceramic substrate improves the density and thermal conductivity of the aluminum nitride ceramic substrate by fine surface modification, addition of a composite sintering aid and strict control of the sintering process. The surface modifier and the composite sintering aid are added to the aluminum nitride powder, the porosity is reduced, the grain structure is optimized through low-temperature densification sintering, the glass phase with poor thermal conductivity is avoided from wrapping the grains, and the thermal conductivity of the substrate is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of ceramic substrate preparation technology, specifically to a method for preparing a high-density, ultra-high thermal conductivity aluminum nitride ceramic substrate. Background Technology

[0002] Aluminum nitride ceramic substrates are widely used in high-power electronic devices, LED lighting, 5G communications, and other fields due to their high thermal conductivity, excellent insulation properties, and coefficient of thermal expansion that matches that of semiconductor materials. In existing technologies, the fabrication of aluminum nitride ceramic substrates typically employs processes such as atmospheric pressure sintering and hot pressing sintering to achieve substrate densification and obtain desired properties.

[0003] However, the existing processes mentioned above still have shortcomings in balancing thermal conductivity and density, cost and mass production: atmospheric pressure sintering often requires the addition of a large amount of sintering aids to achieve densification, which easily leads to the formation of a glassy phase at grain boundaries, thus reducing thermal conductivity; hot pressing sintering can improve density, but the equipment cost is high and the production efficiency is low, making it difficult to achieve mass production of large-area substrates; at the same time, traditional powder pretreatment processes do not sufficiently remove impurities from the powder surface, and defects such as pores and cracks are easily generated after sintering, further restricting the improvement of substrate density and thermal conductivity. Therefore, there is an urgent need for a low-cost, mass-producible method for preparing aluminum nitride ceramic substrates that can simultaneously achieve high density and ultra-high thermal conductivity. Summary of the Invention

[0004] To address the shortcomings of existing technologies, this invention provides a method for preparing a high-density, ultra-high thermal conductivity aluminum nitride ceramic substrate. The technical problem this invention aims to solve is: by optimizing powder surface modification, adding composite sintering aids, and sintering and forming processes, it addresses the issues of difficulty in balancing thermal conductivity and density during atmospheric pressure sintering, high cost of hot pressing sintering equipment, and insufficient impurity removal by traditional powder pretreatment processes.

[0005] To achieve the above objectives, the present invention provides the following technical solution: a method for preparing a high-density, ultra-high thermal conductivity aluminum nitride ceramic substrate, comprising: S1. Select aluminum nitride powder, add a surface modifier to the aluminum nitride powder and ball mill in anhydrous ethanol medium to obtain a slurry, perform solid-liquid separation and drying treatment on the slurry and sieve it to obtain modified aluminum nitride powder; S2. Add a composite sintering aid to the modified aluminum nitride powder and mix evenly. The composite sintering aid is a Y2O3-Dy2O3 composite system. Based on the mass of the modified aluminum nitride powder, the amount of composite sintering aid added is 0.8wt%-1.5wt%, and the mass ratio of Y2O3 to Dy2O3 is 2:1, to obtain a mixed powder. S3. Add a binder to the mixed powder and spray granulate to obtain granules. After loading the granules into a mold, perform dry pressing and cold isostatic pressing treatment in sequence to obtain a green blank. S4. The blank is placed in a debinding furnace for debinding, and heated to 550℃-600℃ at a heating rate of 2℃ / min-5℃ / min and held for 2h-4h to obtain a debinded blank. The debinding atmosphere of the debinding furnace is a mixed gas obtained by mixing air and nitrogen, wherein the volume fraction of air in the mixed gas is 20% and the volume fraction of nitrogen is 80%, so as to reduce the oxygen element in the debinding process while removing the binder. S5. The debonded blank is placed in a nitrogen atmosphere sintering furnace. First, it is heated to 1800℃-1850℃ at 10℃ / min-15℃ / min and held for 0.5h-2h for high-temperature rapid sintering to achieve preliminary sintering and eliminate porosity. Then, it is cooled to 1700℃-1750℃ at 5℃ / min-8℃ / min and held for 8h-12h for low-temperature densification sintering to promote uniform grain growth and optimize the distribution of grain boundary phases so that they transfer to the triangular grain boundaries, thereby avoiding the low thermal conductivity glass phase from encapsulating the aluminum nitride grains. After sintering, it is cooled to room temperature with the furnace to obtain the substrate. The substrate is then ground and polished to obtain the finished aluminum nitride ceramic substrate.

[0006] Preferably, the aluminum nitride powder has a purity of ≥99.9% and a particle size of 0.5μm-2μm; the surface modifier is silane coupling agent KH550, the amount of surface modifier added is 0.1wt%-0.5wt%, the ball milling time is 4h-6h, the ball-to-material ratio is 3:1, and the rotation speed is 200r / min-300r / min.

[0007] Preferably, the slurry is subjected to solid-liquid separation by vacuum filtration, the drying temperature is 80℃-100℃ and the drying time is 12h-24h, and the sieving is performed using a 200-mesh sieve.

[0008] Preferably, the binder is polyvinyl butyral (PVB), the amount of binder added is 5wt%-8wt%, and the particle size of the granules is 50μm-100μm.

[0009] Preferably, the pressure of the dry pressing is 50MPa-80MPa, and the holding time is 1min-2min; the pressure of the cold isostatic pressing is 200MPa-250MPa, and the holding time is 5min-10min.

[0010] Preferably, the nitrogen atmosphere sintering furnace uses a nitrogen atmosphere, and the oxygen content in the nitrogen atmosphere is not greater than 5000 ppm.

[0011] Preferably, the grinding includes double-sided coarse grinding and double-sided fine grinding. The grinding uses diamond abrasive. The diamond abrasive particle size of the double-sided coarse grinding is 8μm-12μm, and the diamond abrasive particle size of the double-sided fine grinding is 0.5μm-4μm. The polishing uses colloidal silica polishing slurry. The surface pressure of the polishing is 6kPa-12kPa, and the polishing time is 15min-30min, so that the surface roughness of the finished aluminum nitride ceramic substrate meets Ra≤0.05μm.

[0012] Preferably, the aluminum nitride ceramic substrate has a relative density ≥99.5%, a thermal conductivity ≥220W / (m·K), and a bending strength ≥300MPa.

[0013] This invention provides a method for preparing a high-density, ultra-high thermal conductivity aluminum nitride ceramic substrate. It has the following beneficial effects: The preparation method of this high-density, ultra-high thermal conductivity aluminum nitride ceramic substrate improves the density and thermal conductivity of the aluminum nitride ceramic substrate through fine surface modification, addition of composite sintering aids, and strict control of the sintering process. The addition of surface modifiers and composite sintering aids to aluminum nitride powder reduces porosity, and the grain structure is optimized through low-temperature densification sintering, which avoids the poor thermal conductivity of the glass phase encapsulating the grains and improves the thermal conductivity of the substrate.

[0014] Nitrogen atmosphere sintering and a special binder removal process were adopted to reduce the introduction of oxygen elements while removing the binder, ensuring high-purity aluminum nitride substrates. The resulting aluminum nitride ceramic substrates have excellent physical properties, meeting the requirements of high-performance electronic devices. Attached Figure Description

[0015] Figure 1 This is a flowchart of the preparation method of the present invention; Figure 2 This is a schematic diagram of the sintering process of the present invention; Figure 3 This is a schematic diagram illustrating the performance and structure of the finished product of this invention. Detailed Implementation

[0016] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0017] Example 1 like Figure 1-3 As shown, this embodiment of the invention provides a method for preparing a high-density, ultra-high thermal conductivity aluminum nitride ceramic substrate, comprising: S1. Select aluminum nitride powder, add a surface modifier to the aluminum nitride powder, and ball mill in anhydrous ethanol medium to obtain a slurry. Perform solid-liquid separation and drying on the slurry, and then sieve to obtain modified aluminum nitride powder. The purity of the aluminum nitride powder is ≥99.9%, and the particle size is 0.5 μm. The surface modifier is silane coupling agent KH550, and the addition amount of the surface modifier is 0.1 wt%. The ball milling time is 4 h, the ball-to-powder ratio is 3:1, and the rotation speed is 200 r / min. The slurry is subjected to solid-liquid separation by vacuum filtration. The drying temperature is 80℃, the drying time is 12 h, and a 200-mesh sieve is used for sieving.

[0018] S2. Add a composite sintering aid to the modified aluminum nitride powder and mix it evenly. The composite sintering aid is a Y2O3-Dy2O3 composite system. Based on the mass of the modified aluminum nitride powder, the amount of composite sintering aid added is 0.8wt%, and the mass ratio of Y2O3 to Dy2O3 is 2:1, to obtain a mixed powder.

[0019] S3. A binder is added to the mixed powder and spray-granulated to obtain granules. The granules are then loaded into a mold and subjected to dry pressing and cold isostatic pressing to obtain a green body. The binder is polyvinyl butyral (PVB), with an addition amount of 5 wt%, and the particle size of the granules is 50 μm. The dry pressing pressure is 50 MPa, and the holding time is 1 min. The cold isostatic pressing pressure is 200 MPa, and the holding time is 5 min.

[0020] S4. Place the blank in a debinding furnace for debinding. Heat the blank to 550℃ at a heating rate of 2℃ / min and hold for 2 hours to obtain a debinded blank. The debinding atmosphere of the debinding furnace is a mixed gas obtained by mixing air and nitrogen. The volume fraction of air in the mixed gas is 20% and the volume fraction of nitrogen is 80%, so as to reduce the oxygen element initiation during the debinding process while removing the binder.

[0021] S5. The unbound preform is placed in a nitrogen atmosphere sintering furnace. First, it is rapidly sintered at 1800℃ (10℃ / min) and held for 0.5 hours to achieve preliminary sintering and eliminate porosity. Then, it is cooled to 1700℃ (5℃ / min) and held for 8 hours for low-temperature densification sintering to promote uniform grain growth and optimize the distribution of grain boundary phases, causing them to transfer towards the triangular grain boundaries. This avoids the low thermal conductivity glass phase encapsulating the aluminum nitride grains. After sintering, the preform is cooled to room temperature in the furnace to obtain the substrate. The substrate is then ground and polished to obtain the finished aluminum nitride ceramic substrate. The nitrogen atmosphere sintering furnace uses a nitrogen atmosphere with an oxygen content not exceeding 5000 ppm. The grinding process includes double-sided rough grinding and double-sided fine grinding, using diamond abrasive. The diamond abrasive particle size is 8μm for double-sided rough grinding and 0.5μm for double-sided fine grinding. Polishing is performed using colloidal silica polishing slurry with a surface pressure of 6kPa and a polishing time of 15min to ensure that the surface roughness of the finished aluminum nitride ceramic substrate meets the requirement of Ra≤0.05μm. The aluminum nitride ceramic substrate has a relative density ≥99.5%, thermal conductivity ≥220W / (m·K), and flexural strength ≥300MPa.

[0022] The preparation method of this invention produces aluminum nitride ceramic substrates by using smaller aluminum nitride powder particle size and lower surface modifier addition. Through appropriate composite sintering aids and controlled sintering temperature, the final prepared ceramic substrate exhibits a thermal conductivity ≥220 W / (m·K), a relative density ≥99.5%, and a flexural strength ≥300 MPa. This demonstrates that despite using lower process parameters, the prepared substrate still meets the basic requirements for thermal conductivity and mechanical properties of high-power electronic devices, making it suitable for electronic applications requiring lower thermal management performance.

[0023] Example 2 This invention provides a method for preparing a high-density, ultra-high thermal conductivity aluminum nitride ceramic substrate, comprising: S1. Select aluminum nitride powder, add a surface modifier to the aluminum nitride powder, and ball mill in anhydrous ethanol medium to obtain a slurry. Perform solid-liquid separation and drying on the slurry, and then sieve to obtain modified aluminum nitride powder. The purity of the aluminum nitride powder is ≥99.9%, and the particle size is 1.25 μm. The surface modifier is silane coupling agent KH550, with an addition amount of 0.3 wt%. The ball milling time is 5 h, the ball-to-powder ratio is 3:1, and the rotation speed is 250 r / min. The slurry is then subjected to solid-liquid separation by vacuum filtration. The drying temperature is 90℃, the drying time is 18 h, and a 200-mesh sieve is used for sieving.

[0024] S2. Add a composite sintering aid to the modified aluminum nitride powder and mix evenly. The composite sintering aid is a Y2O3-Dy2O3 composite system. Based on the mass of the modified aluminum nitride powder, the amount of composite sintering aid added is 1.15wt%, and the mass ratio of Y2O3 to Dy2O3 is 2:1, to obtain a mixed powder.

[0025] S3. A binder is added to the mixed powder and spray-granulated to obtain granules. The granules are then loaded into a mold and subjected to dry pressing and cold isostatic pressing to obtain a green body. The binder is polyvinyl butyral (PVB), with an addition amount of 6.5 wt%, and the particle size of the granules is 75 μm. The dry pressing pressure is 65 MPa, and the holding time is 1.5 min. The cold isostatic pressing pressure is 225 MPa, and the holding time is 7.5 min.

[0026] S4. Place the blank in a debinding furnace for debinding. Heat the blank to 575℃ at a heating rate of 3.5℃ / min and hold for 3 hours to obtain a debinded blank. The debinding atmosphere of the debinding furnace is a mixed gas obtained by mixing air and nitrogen. The volume fraction of air in the mixed gas is 20% and the volume fraction of nitrogen is 80%, so as to reduce the oxygen element initiation during the debinding process while removing the binder.

[0027] S5. The unbound blank is placed in a nitrogen atmosphere sintering furnace. First, it is rapidly sintered at 12.5℃ / min to 1825℃ and held for 1.25h to achieve preliminary sintering and eliminate porosity. Then, it is cooled at 6.5℃ / min to 1725℃ and held for 10h for low-temperature densification sintering to promote uniform grain growth and optimize the distribution of grain boundary phases, causing them to transfer towards the triangular grain boundaries. This avoids the low thermal conductivity glass phase encapsulating the aluminum nitride grains. After sintering, the blank is cooled to room temperature in the furnace to obtain the substrate. The substrate is then ground and polished to obtain the finished aluminum nitride ceramic substrate. The nitrogen atmosphere sintering furnace uses a nitrogen atmosphere with an oxygen content not exceeding 5000ppm. The grinding process includes double-sided rough grinding and double-sided fine grinding, using diamond abrasive. The diamond abrasive particle size is 10μm for double-sided rough grinding and 2.25μm for double-sided fine grinding. Polishing is performed using colloidal silica polishing slurry with a surface pressure of 9kPa and a polishing time of 22.5min to ensure that the surface roughness of the finished aluminum nitride ceramic substrate meets the requirement of Ra≤0.05μm. The aluminum nitride ceramic substrate has a relative density ≥99.5%, thermal conductivity ≥220W / (m·K), and flexural strength ≥300MPa.

[0028] Using aluminum nitride powder with a particle size of 1.25 μm and a surface modifier dosage of 0.3 wt%, an aluminum nitride ceramic substrate was prepared with a thermal conductivity ≥220 W / (m·K), a relative density ≥99.5%, and a flexural strength ≥300 MPa. By adjusting the powder particle size and the amount of modifier added, the overall performance of the substrate was optimized, and in terms of surface precision, the surface roughness Ra ≤ 0.05 μm was achieved. The process conditions in this embodiment improved the thermal conductivity and mechanical strength of the substrate, making it suitable for high-power thermal management applications with high surface precision requirements, such as high-precision electronic devices and heat dissipation systems.

[0029] Example 3 This invention provides a method for preparing a high-density, ultra-high thermal conductivity aluminum nitride ceramic substrate, comprising: S1. Select aluminum nitride powder, add a surface modifier to the aluminum nitride powder, and ball mill in anhydrous ethanol medium to obtain a slurry. Perform solid-liquid separation and drying on the slurry, and then sieve to obtain modified aluminum nitride powder. The purity of the aluminum nitride powder is ≥99.9%, and the particle size is 2μm. The surface modifier is silane coupling agent KH550, with an addition amount of 0.5wt%. The ball milling time is 6h, the ball-to-powder ratio is 3:1, and the rotation speed is 300r / min. The slurry is then subjected to solid-liquid separation by vacuum filtration. The drying temperature is 100℃, the drying time is 24h, and a 200-mesh sieve is used for sieving.

[0030] S2. Add a composite sintering aid to the modified aluminum nitride powder and mix it evenly. The composite sintering aid is a Y2O3-Dy2O3 composite system. Based on the mass of the modified aluminum nitride powder, the amount of composite sintering aid added is 1.5wt%, and the mass ratio of Y2O3 to Dy2O3 is 2:1, to obtain a mixed powder.

[0031] S3. A binder is added to the mixed powder and spray-granulated to obtain granules. The granules are then loaded into a mold and subjected to dry pressing and cold isostatic pressing to obtain a green body. The binder is polyvinyl butyral (PVB), with an addition amount of 8 wt%, and the particle size of the granules is 100 μm. The dry pressing pressure is 80 MPa, and the holding time is 2 min. The cold isostatic pressing pressure is 250 MPa, and the holding time is 10 min.

[0032] S4. Place the blank in a debinding furnace for debinding. Heat the blank to 600℃ at a heating rate of 5℃ / min and hold for 4 hours to obtain a debinded blank. The debinding atmosphere of the debinding furnace is a mixed gas obtained by mixing air and nitrogen. The volume fraction of air in the mixed gas is 20% and the volume fraction of nitrogen is 80%, so as to reduce the oxygen element initiation during the debinding process while removing the binder.

[0033] S5. The unbound preform is placed in a nitrogen atmosphere sintering furnace. First, it is rapidly sintered at 1850℃ (15℃ / min) for 2 hours to achieve preliminary sintering and eliminate porosity. Then, it is rapidly cooled to 1750℃ (8℃ / min) for 12 hours to achieve low-temperature densification sintering, promoting uniform grain growth and optimizing the distribution of grain boundary phases, causing them to transfer towards the triangular grain boundaries. This avoids the low thermal conductivity glass phase encapsulating the aluminum nitride grains. After sintering, the preform is cooled to room temperature in the furnace to obtain the substrate. The substrate is then ground and polished to obtain the finished aluminum nitride ceramic substrate. The nitrogen atmosphere sintering furnace uses a nitrogen atmosphere with an oxygen content not exceeding 5000 ppm. The grinding process includes double-sided rough grinding and double-sided fine grinding, using diamond abrasive. The diamond abrasive particle size is 12μm for double-sided rough grinding and 4μm for double-sided fine grinding. Polishing is performed using colloidal silica polishing slurry with a surface pressure of 12kPa and a polishing time of 30min, to ensure that the surface roughness of the finished aluminum nitride ceramic substrate meets the requirement of Ra≤0.05μm. The aluminum nitride ceramic substrate has a relative density ≥99.5%, thermal conductivity ≥220W / (m·K), and flexural strength ≥300MPa.

[0034] Under higher process parameters—using aluminum nitride powder with a particle size of 2 μm and a surface modifier addition of 0.5 wt%—the prepared aluminum nitride ceramic substrate exhibits superior performance. By employing higher levels of composite sintering aids and higher sintering temperatures, the substrate maintains a thermal conductivity ≥220 W / (m·K), a flexural strength ≥300 MPa, and a surface roughness Ra≤0.05 μm. These higher process parameters further improve the material's density and strength, making it suitable for high-end electronic applications with extremely high requirements for thermal management and mechanical strength, such as high-power processors and advanced heat sinks. These process conditions maximize the material's performance and improve its stability and durability under high-temperature environments.

[0035] Example 4 This embodiment is based on a method for preparing a high-density, ultra-high thermal conductivity aluminum nitride ceramic substrate. By comparing the effects of different processing conditions, the relative density, thermal conductivity, and flexural strength of the aluminum nitride ceramic substrate are evaluated. The specific implementation method is as follows: 1. Material selection and surface modification Experiment A: Aluminum nitride powder: Aluminum nitride powder with a purity of ≥99.9% and a particle size of 0.5μm is selected.

[0036] Surface modifier: Use 0.1wt% silane coupling agent KH550 to ensure good powder dispersibility.

[0037] Ball milling conditions: The ball milling time is set to 4 hours, the ball-to-material ratio is 3:1, and the rotation speed is 200 r / min to ensure that the modifier is evenly coated on the powder surface.

[0038] Slurry treatment: The slurry is separated into solid and liquid by vacuum filtration, dried at 80℃ for 12 hours, and sieved through a 200-mesh sieve.

[0039] Features: The relatively small particle size and low amount of surface modifier added are expected to result in higher powder surface activity and better densification effect.

[0040] Experiment B: Aluminum nitride powder: Aluminum nitride powder with a purity of ≥99.9% and a particle size of 1.25μm is selected.

[0041] Surface modifier: 0.3 wt% silane coupling agent KH550 is used to enhance the dispersibility of the powder.

[0042] Ball milling conditions: The ball milling time is set to 5 hours, the ball-to-material ratio is 3:1, and the rotation speed is 250 r / min. Increasing the ball milling time and rotation speed helps to achieve uniform coating of the modifier and uniform particle size.

[0043] Slurry treatment: The slurry is separated into solid and liquid by vacuum filtration, dried at 90℃ for 18 hours, and sieved through a 200-mesh sieve.

[0044] Features: Compared with Experiment A, the ball milling time and speed were increased, and a higher surface modification dosage was used, which is expected to result in finer powder particles and higher dispersibility.

[0045] Experiment C: Aluminum nitride powder: Aluminum nitride powder with a purity of ≥99.9% and a particle size of 2μm is selected.

[0046] Surface modifier: 0.5 wt% silane coupling agent KH550 is used to further improve the dispersibility of the powder.

[0047] Ball milling conditions: The ball milling time is set to 6 hours, the ball-to-material ratio is 3:1, and the rotation speed is 300 r / min. Extending the ball milling time and increasing the rotation speed ensures better coating of the surface modifier.

[0048] Slurry treatment: The slurry is separated into solid and liquid by vacuum filtration, dried at 100℃ for 24 hours, and sieved through a 200-mesh sieve.

[0049] Features: Larger particle size and higher amount of surface modifier added. Longer ball milling time and higher speed are expected to make the powder particles more uniform and the modification effect better, but may affect the control of porosity during sintering.

[0050] Surface modification reduces powder agglomeration and improves the compatibility between the powder and sintering aids, laying the foundation for subsequent high-density sintering. After surface modification, the modifier can be uniformly coated on the powder surface, improving the powder's flowability and dispersibility, which helps reduce non-uniformity during subsequent sintering.

[0051] 2. Addition of composite sintering aids Experiment A: Sintering aid: 0.8 wt% of Y2O3-Dy2O3 composite system is added, with a mass ratio of Y2O3 to Dy2O3 of 2:1. The low dosage of the aid is intended to promote densification during sintering.

[0052] Features: Lower sintering aid addition may have a milder effect on the sintering process, making it suitable for fine-particle aluminum nitride powder.

[0053] Experiment B: Sintering aid: 1.15 wt% of Y2O3-Dy2O3 composite system was added, with a mass ratio of Y2O3 to Dy2O3 of 2:1, which increased the amount of sintering aid compared to Experiment A.

[0054] Features: Higher sintering aid dosage helps to improve the density of sintering, increase thermal conductivity and flexural strength.

[0055] Experiment C: Sintering aid: Add 1.5wt% of Y2O3-Dy2O3 composite system, with a mass ratio of Y2O3 to Dy2O3 of 2:1, which is the largest amount of sintering aid added.

[0056] Features: High amounts of sintering aids contribute to stronger densification and are expected to have a greater impact on thermal conductivity and strength. However, excessive sintering aids may also bring other side effects, such as excessive grain growth.

[0057] The use of Y2O3-Dy2O3 composite sintering aid can reduce the sintering temperature and decrease the content of grain boundary glass phase compared to a single aid, thereby improving thermal conductivity.

[0058] 3. Molding and Sintering Process Experiment A: Binder: 5 wt% polyvinyl butyral is used, and the particle size of the granules is 50 μm.

[0059] Molding pressure: Dry pressing pressure is 50MPa, and cold isostatic pressing pressure is 200MPa.

[0060] Sintering process: Under nitrogen atmosphere, the temperature is increased to 1800℃ at 10℃ / min, held for 0.5 hours, then decreased to 1700℃ and held for 8 hours.

[0061] Features: Lower sintering temperature and shorter holding time, suitable for powders with smaller particle size, and expected to achieve better densification effect.

[0062] Experiment B: Binder: 6.5 wt% polyvinyl butyral is used, and the particle size of the granules is 75 μm.

[0063] Molding pressure: Dry pressing pressure 65MPa, cold isostatic pressing pressure 225MPa.

[0064] Sintering process: Under nitrogen atmosphere, the temperature is increased to 1825℃ at 12.5℃ / min, held for 1.25 hours, then decreased to 1725℃ and held for 10 hours.

[0065] Features: Higher sintering temperature and longer holding time will help improve the density of the substrate and promote uniform grain growth.

[0066] Experiment C: Binder: 8 wt% polyvinyl butyral is used, and the particle size of the granules is 100 μm.

[0067] Molding pressure: 80MPa for dry pressing and 250MPa for cold isostatic pressing.

[0068] Sintering process: Under nitrogen atmosphere, the temperature is increased to 1850℃ at 15℃ / min, held for 2 hours, then cooled to 1750℃ and held for 12 hours.

[0069] Features: Highest sintering temperature and holding time; larger particle size and higher binder dosage are expected to further improve the density and thermal conductivity of the substrate.

[0070] The dry pressing-cold isostatic pressing composite molding process reduces the internal porosity of the green blank, ensuring uniform density and providing a good foundation for subsequent sintering. The two-step sintering process ensures substrate densification, avoids excessive grain size caused by prolonged high-temperature holding, reduces the risk of decreased flexural strength, and improves the overall performance of the substrate.

[0071] 4. Final Performance Testing and Comparison After sintering, the three groups of experiments underwent tests to measure relative density, thermal conductivity, and flexural strength. The specific testing methods are as follows: Relative density test: The relative density is measured using the Archimedes method.

[0072] The sample was placed in water and weighed. The volume of the sample was calculated using the principle of buoyancy, and the relative density was calculated based on the sample's mass. The theoretical density of aluminum nitride is approximately 3.26 g / cm³. 3 .

[0073] Thermal conductivity test: Thermal conductivity is tested using the laser flash method.

[0074] A laser pulse is applied to the sample surface, and the temperature change is recorded. The thermal conductivity of the sample is then calculated using the thermal diffusion equation. A specialized laser thermal conductivity meter is used for the test.

[0075] Bending strength test: The bending strength is measured using the three-point bending test method.

[0076] The sample is placed on two supports, and a gradually increasing load is applied between them until the sample breaks. The maximum load at fracture is recorded. Standard-sized samples are used during testing in accordance with industry standards, and the testing process is strictly carried out according to standardized equipment and procedures to ensure the accuracy of the test results.

[0077] The test results are as follows: Table 1: Performance Test Results.

[0078]

[0079] 5. Comparative Analysis and Conclusions Relative density: The relative density of all experimental groups met the design requirements, with Experiment C having the highest relative density, indicating that higher sintering temperature and longer holding time helped improve density.

[0080] Thermal conductivity: Experiment C showed the highest thermal conductivity, indicating that higher sintering temperature and additive dosage can improve thermal conductivity.

[0081] Flexural strength: Experiment A exhibited the highest flexural strength; smaller grain size and lower sintering temperature contributed to the greater mechanical strength. Experiment C showed the lowest flexural strength; although it had good thermal conductivity, excessive grain growth may have negatively impacted its mechanical properties.

[0082] In summary, different particle sizes, sintering aid dosages, and sintering processes affect the performance of aluminum nitride ceramic substrates. Experiment A exhibits higher flexural strength, while Experiment C demonstrates the best thermal conductivity. Based on practical application requirements, the most suitable process conditions can be selected for optimization. The aluminum nitride ceramic substrate of this invention achieves a relative density ≥99.5%, thermal conductivity ≥220 W / (m·K), and flexural strength ≥300 MPa. Furthermore, the process requires no expensive equipment, reducing production costs by more than 30%, making it suitable for industrial mass production.

[0083] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a high-density, ultra-high thermal conductivity aluminum nitride ceramic substrate, characterized in that, include: S1. Select aluminum nitride powder, add a surface modifier to the aluminum nitride powder and ball mill in anhydrous ethanol medium to obtain a slurry, perform solid-liquid separation and drying treatment on the slurry and sieve it to obtain modified aluminum nitride powder; S2. Add a composite sintering aid to the modified aluminum nitride powder and mix evenly. The composite sintering aid is a Y2O3-Dy2O3 composite system. Based on the mass of the modified aluminum nitride powder, the amount of composite sintering aid added is 0.8wt%-1.5wt%, and the mass ratio of Y2O3 to Dy2O3 is 2:1, to obtain a mixed powder. S3. Add a binder to the mixed powder and spray granulate to obtain granules. After loading the granules into a mold, perform dry pressing and cold isostatic pressing treatment in sequence to obtain a green blank. S4. The blank is placed in a debinding furnace for debinding, and heated to 550℃-600℃ at a heating rate of 2℃ / min-5℃ / min and held at that temperature for 2h-4h to obtain a debinded blank. The debinding atmosphere of the debinding furnace is a mixed gas obtained by mixing air and nitrogen, wherein the volume fraction of air in the mixed gas is 20% and the volume fraction of nitrogen is 80%. S5. The debonded blank is placed in a nitrogen atmosphere sintering furnace. First, it is heated to 1800℃-1850℃ at 10℃ / min-15℃ / min and held for 0.5h-2h for high-temperature rapid sintering. Then, it is cooled to 1700℃-1750℃ at 5℃ / min-8℃ / min and held for 8h-12h for low-temperature densification sintering. After sintering, it is cooled to room temperature with the furnace to obtain a substrate. The substrate is then ground and polished to obtain the finished aluminum nitride ceramic substrate.

2. The method for preparing a high-density, ultra-high thermal conductivity aluminum nitride ceramic substrate according to claim 1, characterized in that: The aluminum nitride powder has a purity of ≥99.9% and a particle size of 0.5μm-2μm; the surface modifier is silane coupling agent KH550, and the amount of surface modifier added is 0.1wt%-0.5wt%; the ball milling time is 4h-6h, the ball-to-material ratio is 3:1, and the rotation speed is 200r / min-300r / min.

3. The method for preparing a high-density, ultra-high thermal conductivity aluminum nitride ceramic substrate according to claim 1, characterized in that: The slurry is subjected to solid-liquid separation by vacuum filtration. The drying process is carried out at a temperature of 80℃-100℃ for 12h-24h. A 200-mesh sieve is used for sieving.

4. The method for preparing a high-density, ultra-high thermal conductivity aluminum nitride ceramic substrate according to claim 1, characterized in that: The binder is polyvinyl butyral (PVB), and the amount of binder added is 5wt%-8wt%. The particle size of the granules is 50μm-100μm.

5. The method for preparing a high-density, ultra-high thermal conductivity aluminum nitride ceramic substrate according to claim 1, characterized in that: The pressure for dry pressing is 50MPa-80MPa, and the holding time is 1min-2min. The pressure for cold isostatic pressing is 200MPa-250MPa, and the holding time is 5min-10min.

6. The method for preparing a high-density, ultra-high thermal conductivity aluminum nitride ceramic substrate according to claim 1, characterized in that: The nitrogen atmosphere sintering furnace uses a nitrogen atmosphere, and the oxygen content in the nitrogen atmosphere is no more than 5000 ppm.

7. The method for preparing a high-density, ultra-high thermal conductivity aluminum nitride ceramic substrate according to claim 1, characterized in that: The grinding includes double-sided coarse grinding and double-sided fine grinding. The grinding uses diamond abrasive. The diamond abrasive particle size of the double-sided coarse grinding is 8μm-12μm, and the diamond abrasive particle size of the double-sided fine grinding is 0.5μm-4μm. The polishing uses colloidal silica polishing slurry. The surface pressure of the polishing is 6kPa-12kPa, and the polishing time is 15min-30min.

8. The method for preparing a high-density, ultra-high thermal conductivity aluminum nitride ceramic substrate according to claim 1, characterized in that: The aluminum nitride ceramic substrate has a relative density ≥99.5%, thermal conductivity ≥220W / (m·K), and bending strength ≥300MPa.